THE DEVELOPMENT OF ANDROID-BASED SUBJECTS TO IMPROVE STUDENTS’ PRONUNCIATION - Hesti Wahyuni Anggraini; Hardini Novianti; Ali Bardadi (Universitas Negeri Medan, 2018)
The purpose of this study is to find out how to develop an android application that can be used to support students’ needs and implement the application in learning process in order to improve students' pronunciation ability. Sampling was done by purposive sampling and got 40 students from English Education Study Program Faculty of Teacher Training and Education of Universitas Sriwijaya in the first intake of academic year 2017/2018. The instrument of data collection is questionnaire. The analysis technique is the analysis of questionnaire that aims at the affective aspects using this application during the learning process. To conclude, overall, the students can understand and use android application well and affectively effects the students behavior.